The effect of Streptococcus agalactiae infection in tilapia exposed to different colors of light - Tan, Sheng Jen (2018)
Tilapia infected with Streptococcus agalactiae were exposed to different colors of light before and after infection in order to identify the ideal color that can maximize feed intake, minimize mortality rate, maintain optimum white blood cell (WBC) count and cortisol level. The hypothesis is feed intake, mortality rate, WBC count and cortisol level of tilapia exposed to blue and red lights will have significant differences compared to those exposed to white light. The fish were first exposed to white, blue and red light respectively for 2 weeks before they were challenged withStreptococcus agalactiae infection. Blood samples were collected before and after bacterial challenge to measure WBC count and cortisol level, while the feed intake and mortality rate were recorded throughout the project. The results showed no significant difference (P>0.05) in feed intake, mortality rate and WBC count among all the group of fish. This was also the same in cortisol level of fish exposed to blue light when compared to fish exposed to white light. However, fish exposed to red light had significant difference (P<0.05) in cortisol level compared to fish exposed to white light. Therefore, red light exposure to tilapia is stressful as indicated by higher cortisol level.
Also available in CD-ROM format.
Project paper (D.V.M.) - Universiti Putra Malaysia, 2018.